2004
DOI: 10.1152/physiolgenomics.00097.2003
|View full text |Cite
|
Sign up to set email alerts
|

Steroid sulfatase gene variation and DHEA responsiveness to resistance exercise in MERET

Abstract: Genetic influences and endurance exercise have been shown to alter circulating concentrations of dehydroepiandrosterone (DHEA) and its sulfated conjugate, DHEAS. We hypothesized that acute resistance exercise (RE) and training (RET) would increase DHEA steroids, and the magnitude of the increase would be influenced by a steroid sulfatase (STS) gene variation. Fasting blood samples were collected before and after the first (S1) and last (S30) session of a 10-wk RET program in 62 men and 58 women [age: 21.0 yr (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
(48 reference statements)
0
21
1
Order By: Relevance
“…Riechman et al (29) reported that acute resistance exercise increased blood DHEAS levels. The exercise-induced increases in DHEAS concentrations have been attributed to an increased rate of secretion from the adrenal cortex in response to ACTH stimulation (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Riechman et al (29) reported that acute resistance exercise increased blood DHEAS levels. The exercise-induced increases in DHEAS concentrations have been attributed to an increased rate of secretion from the adrenal cortex in response to ACTH stimulation (16).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the resting serum level of testosterone in women is about 10 times lower than that in tnen. Riechman et al (29) showed that acute resistance exercise induces increased DHEAS, a peripheral precursor of testosterone, in both men and women. These results indicated that there are sex differences in basal anabolic homione levels and responses to exercise.…”
mentioning
confidence: 99%
“…STS expression increases in human fallopian epithelial cells during the early luteal phase and recedes during the follicular phase of the menstrual cycle [Yanaihara et al, 2001]. STS activity/expression is also transiently increased during acute or chronic exercise [Riechman et al, 2004] and in the adrenals of stressed animals [Dominguez et al, 1975]. STS activity becomes deregulated as part of several hormone-mediated disorders.…”
mentioning
confidence: 99%
“…The underlying nature for this discrepancy is unknown. Variation in the DHEA-S level, which can be influenced by environmental and genetic factors (Riechman et al, 2004;Smit et al, 2005), could be one possibility that explains the different results for this aspect in response to altitude challenge.…”
mentioning
confidence: 99%